Conservative financial reporting, debt covenants, and the agency costs of debt - Guay, Wayne R. (Journal of Accounting and Economics, 2008)
Considerable research has documented the role of debt covenants and conservative financial accounting in addressing agency conflicts between lenders and borrowers. Beatty, A., Weber, J., and Yu, J. [2008. Conservatism and debt. Journal of Accounting and Economics, forthcoming] document interesting, but mixed, findings on the relation between debt covenants and conservative accounting, and the extent to which the two contracting mechanisms act as substitutes or complements. In this paper, I discuss the economic roles of financial reporting, debt covenants, and conservatism within the debt contracting environment, and attempt to fit BWY's findings within this context.